What Factors Influence The Use Of Traditional Medicine In Adults?: A Scoping Review - Teuku Reza Fadly; Sutopo Patria Jati; Ayun Sriatmi (Eduvest - Journal of Universal Studies, 2024)
The use of traditional medicine has been an integral part of healthcare in various countries, including Indonesia. This study aims to analyze the factors influencing adults' decisions to use traditional medicine, focusing on socio-demographic aspects, health conditions, and cultural preferences. Results from cross-country studies in Sudan, Jordan, Cameroon, Ethiopia, and Nigeria reveal that age, gender, education level, and health conditions significantly impact the choice of traditional medicine. Additionally, cultural preferences and inherited knowledge contribute significantly to these decisions. The findings suggest that it is crucial to integrate traditional medicine into modern healthcare systems, along with strengthening regulations and education regarding the safety and efficacy of traditional medicine to ensure better health outcomes.